Histoplasmosis in the Anal Canal: Case Report and Literature Review - Santos, Gabriel Driemeier dos; Manna, Augusto Araboni Mendes Barcelos; Santos, Carlos Henrique Marques dos (Journal of Coloproctology, 2023)
We herein present the case of a patient with anal condylomatosis concomitant with histoplasmosis, whose diagnosis was only possible through the collection of material and the subsequent evidence of a primary pulmonary focus. Histoplasmosis is a fungal disease whose contamination occurs through the respiratory route, and it can spread to the digestive tract, but the anus is rarely affected. It is important to have a high degree of suspicion to make the diagnosis, especially in immunosuppressed patients.
Keywords: histoplasmosis; anal canal; condyloma acuminatum; digestive system abnormalities